Dental and Oral Health Status of Elementary School Children in Central Lampung - Andayani, Lia Hapsari; Soulissa, Abdul Gani; Lestari, Sri (Indonesian Dental Association, 2021)
Introduction: Dental caries and gingivitis are the most prevalent oral health problems in Indonesian elementary school children. Predictors that are significantly associated with dental caries and gingivitis in children are the parents’ socioeconomic status and children’s oral health behavior. Terbanggi Besar district is the largest area and population in Lampung Province. The lack of updated dental and oral health data needs to be refined to address oral health disparities and achieve improvements. Objectives: This study aimed to assess the dental and oral health status of grade V and VI elementary school children in Terbanggi Besar district, Central Lampung. Method: This cross-sectional study elected 410 students from 5 public elementary schools using convenience sampling. Sociodemographic and oral health behavior data were retrieved from a self-administered questionnaire. In addition, a clinical examination consisted of the Decayed, Missing, and Filled Teeth (DMFT) index, the Gingival Index (GI), and the Simplified Oral Hygiene Index (OHIS). The Mann-Whitney statistical test was used to analyze the differences in dental caries severity and gingival status between selected variables. Results: Dental caries was present in 75.6% of children, while gingivitis was present in 52% of children. The mean DMFT score was significantly higher in children with poor oral hygiene (2.80 + 2.67, p = 0.001). The mean GI score was significantly higher in children aged 12 years old or above (0.37 + 0.48, p = 0.025) and in those that had unemployed fathers (0.25 + 0.29, p = 0.030) and poor oral hygiene (0.31 + 0.40, p = 0.000). Conclusion: Improving dental and oral health promotion with regard to elementary school children is highly recommended. The dental and oral health status of grade V and VI elementary school children in Terbanggi Besar district in Central Lampung was found to be moderate, with a high prevalence of dental caries.